Gene expression markers in horse articular chondrocytes: Chondrogenic differentiaton IN VITRO depends on the proliferative potential and ageing. Implication for tissue engineering of cartilage. (February 2020) - De Angelis, Elena; Cacchioli, Antonio; Ravanetti, Francesca; Bileti, Rossana; Cavalli, Valeria; Martelli, Paolo; Borghetti, Paolo
Abstract: Chondrocyte dedifferentiation is a key limitation in therapies based on autologous chondrocyte implantation for cartilage repair. Articular chondrocytes, obtained from (metacarpophalangeal and metatarsophalangeal) joints of different aged horses, were cultured in monolayer for several passages (P0 to P8). Cumulative Populations Doublings Levels (PDL) and gene expression of relevant chondrocyte phenotypic markers were analysed during culturing. Overall data confirmed that, during proliferation in vitro, horse chondrocytes undergo marked morphological and phenotypic alterations of their differentiation status. Particularly, the dedifferentiation started early in culture (P0-P1) and was very marked at P3 subculture (PDL 4–6): proliferative phase after P3 could be critical for maintenance/loss of differentiation potential. In elderly animals, chondrocytes showed aspects of dedifferentiation shortly after their isolation, associated with reduced proliferative capacity. Regarding the gene expression of major cartilage markers (Col2, Aggrecan, SOX9) there was a very early reduction (P1) in proliferating chondrocytes independent of age. The chondrocytes from adult donors showed a more stable expression (up to P3) of some (Col6, Fibromodulin, SOX6, TGβ1) markers of mature cartilage; these markers could be tested as parameter to determine the dedifferentiation level. This study can provide parameters to identify up to which "culture step" chondrocytes for implantation with a conserved phenotypic potential can be obtained, and to test the efficiency of biomaterial scaffold or chondroinductive media/signals to maintain/recover the chondrocyte phenotype. Moreover, the determination of levels and time related expression of these markers can be useful during the chondroinduction of mesenchymal stem cells. Highlights: Proliferative phase after P3 seems to be critical for maintenance/loss of differentiation potential; Chondrocytes from elderly horses go through an early dedifferentiation and a reduction of their proliferative capacity; Related trend of Col6, fibromodulin, Sox6 and TGF-β1 to changes of Runx2 for monitoring of the dedifferentiation process. Chondrocytes from adult donors showed a more stable expression of mature cartilage markers.